STUDENTS’ AND TEACHER’S PERCEPTION OF TASK-BASED LANGUAGE TEACHING AND THE IMPLEMENTATION IN LISTENING CLASS - Sahrawi Sahrawi (IKIP PGRI Pontianak, 2017)
The purposes of this research were to know the perception of students and teacher about task-based language teaching (TBLT), the ways used by the teacher in the implementation of TBLT, and the ways of the students in perceiving and completing a task in the listening class. This case study was conducted at IKIP-PGRI Pontianak where the sample were one teacher and twelve students in the first semester. The techniques of collecting data were interview, observation, and documentation. The data were analyzed by using grounded theory. The research findings showed that: (1) The students and the teacher believed that TBLT helped them in the listening class, it could motivate learners to be more active by using the target language; (2) The teacher could present the instruction clearly and optimally by using spoken and written form; and (3) each student perceived and accomplished the task in different way. Keywords: perception, TBLT, listening class.